Why was Keynes opposed to reparations and Carthaginian peace? - Elise S. Brezis (Bar-Ilan University, Department of Economics, 2022)
The Economic Consequences of the Peace was first published in 1919, and since then, changed the economic discourse surrounding reparations and Carthaginian peace. This paper specifies how three elements hinted at in the introduction of the Economic Consequences of the Peace - social classes, national sovereignty, and the international political system - can explain Keynes' assessment of Carthaginian peace. The paper analyzes the optimality of reparations in the context of these three elements. I show that in the situation of a hegemonic country, all classes - the working class as well as the elite - opt for no reparations. But, in a balance of power context, wherein no single actor on the international scene possesses hegemonic status, the working class will choose harsh reparations, while the transnational elite and Keynes will not.
Keywords: B17; B27; E12; F30; 330; Balance of Power; Carthaginian Peace; Hegemony; Reparations; National Sovereignty